The Christian Concern with History - Cadoux, C. J. (The journal of religion, 1923)
Amid all the variations in the interpretation of past events, there is general agreement that a knowledge of history is indispensable to an understanding of living issues. Christianity has rested its case on the historicity of certain narratives in the New Testament. Recognizing the crucial importance of positive convictions here, the present article argues that an untrammeled use of historical criticism is necessary. Some aspects and implications of this criticism are pointed out.